The contribution of focusing attention to the shooting accuracy of the smallest handball - Saidi, Abdelmadjid; بن شرنين عبد الحميد (sports creativity, 2025)
The study aimed to identify the contribution of focusing attention to the shooting accuracy of the smallest handball, which used the searcher descriptive approach, the sample included MC al-bouira players selected in a deliberate cover 20 athlete, and use the researcher tested focusing attention and shooting accuracy, after data collection and deal with the appropriate statistical methodology (IBM SPSS V 25), reached a reverse correlation (negative) strong and statistically function between focus and shooting accuracy of the smallest handball, contributing the level of attention by 80% in the level of precision shooting, a researcher in the development of the attention focused more on smallest handball to a strong relationship and statistically function between him and shooting accuracy, Study the relationship between